PERAN PENDIDIKAN ISLAM MENURUT PEMIKIRAN AZYUMARDI AZRA: (Literasi Tokoh Pendidikan Terhadap Pendidikan Islam) - Murtadha Murtadha (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
Azyumardi Azra narrows the purpose and role of education into two parts, namely general goals and specific goals. According to Azyumardi Azra, the purpose of Islamic education is inseparable from the purpose of human life in Islam, namely to create personal servants of Allah who always fear Him, and can achieve a happy life in this world and in the hereafter. In the context of social-society, nation and state, this pious person becomes rahmatan lil 'alamin, both on a small and large scale. The purpose of human life in Islam is what can also be called the general goal or end of Islamic education.